Study of Cloud Computing & Databases: A study on the impact of information technology on banking products and services in Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2011)
In Present study we have tried to  assess the new products and services available from the banks to the customers in Haryana, to ascertain the impact of information technology on the bank deals in Haryana, to ascertain the marketing strategies adopted by the bank branches in Haryana for marketing their products and services, to examine the extent of acceptance of the banking products and services by the customers in Haryana, and to evaluate the attitude of the bank personnel vis-a-vis. customers towards marketing of new products and services of banks